Research of Cascade Control with an Application to Central Air-Conditioning System - Jiang-Jiang Wang; Chun-Fa Zhang; You-Yin Jing (2007 International Conference on Machine Learning and Cybernetics, 2007)
The heat exchanger and air-conditioning space in the central air-conditioning system are modeled in mathematic. Based on the models, we propose a cascade control strategy for temperature control of air-conditioning system. The setpoint response controller in the cascade control system is designed in terms of the robust control H2 optimal performance specification. According to the system operation requirement for disturbance rejection, a closed-loop for rejecting disturbance signals is configured and the controller in internal loop is figured out by proposing the desired closed-loop complementary function. Finally, the three controllers, the designed cascade control, traditional cascade PID control and single PID control are simulated in central air-conditioning system. It is found that the setpoint response, the disturbance rejection, the robust and the performance of the designed cascade control system are better.